"I Do Not Take My Medicine while Hiding" - A Longitudinal Qualitative Assessment of HIV Discordant Couples' Beliefs in Discordance and ART as Prevention in Uganda. - Rachel King; Jiho Kim; Mastula Nanfuka; Murisho Shafic; Maureen Nyonyitono; Florence Galenda; David Moore (PLoS ONE, 2017)
BACKGROUND:HIV negative members of serostatus discordant couples are at high risk for HIV acquisition, but few interventions are in place to target them in sub-Saharan Africa. METHODS:In this study, we interviewed 28 couples, 3 times over a period of one year to understand their perceptions and attitudes around discordance, their relationship dynamics, their HIV risk behaviour, their beliefs and attitudes about antiretroviral therapy (ART) and their views of the community perceptions of discordance and treatment for HIV. RESULTS:Findings revealed that at baseline there were multiple complex explanations and interpretations about discordance among discordant couples and their surrounding community. Shifts in beliefs and attitudes about discordance, HIV risk reduction and ART over time were enabled through re-testing negative members of discordant couples and repeat counselling but some beliefs remain solidly embedded in cultural imperatives of the importance of childbearing as well as culturally determined and enforced gender roles. CONCLUSIONS:Interventions that aim to target discordant couples must embrace the complex and dynamic understandings of HIV diagnosis and treatment in context of fluid relationships, and changing beliefs about HIV risk and treatment.